2015
DOI: 10.1007/s11085-015-9567-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfides on the Corrosion Behavior of Inconel 600 and Incoloy 825 in Supercritical Water

Abstract: Corrosion tests of Inconel 600 and Incoloy 825 were performed in supercritical water containing sulfides at 520°C and 25 MPa. The scales formed on Inconel 600 consisted of a thick outer layer of almost pure Ni 3 S 2 and an inner layer predominantly of Cr-rich spinels with a Ni 3 S 2 network inside. The scales of Incoloy 825 also had a multilayered structure. The outer layer primarily consisted of Ni 3 S 2 and (Ni,Fe) 3 S 4, followed by a thicker intermediate mixture layer of chromium-rich oxides, Ni 3 S 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 52 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…Taking magnetite as an example, which has been studied extensively as a function of oxygen partial pressure, the critical boundary oxygen partial pressure (pc,o2) is ~10 −6 atm at 1200 °C [48], ~10 −8.3 atm at 1000 °C [46], ~10 −20 atm at 600 °C [11], ~10 −25 –10 −22 atm at 500 °C [11,46], and ~10 −30 atm at 400 °C [11]. Previous studies have suggested that the rate-controlling step in the corrosion of ferritic-martensitic steels in SCW is the outward diffusion of iron and that the inner layer generally plays the role of the protective barrier layer [7,8,10,12,30,33,51]. However, the inner layer grows into the metal phase at the metal/inner layer interface [52,53], and the cations diffusing outwards through the inner layer are not involved in the growth of the inner layer into the metal.…”
Section: Resultsmentioning
confidence: 99%
“…Taking magnetite as an example, which has been studied extensively as a function of oxygen partial pressure, the critical boundary oxygen partial pressure (pc,o2) is ~10 −6 atm at 1200 °C [48], ~10 −8.3 atm at 1000 °C [46], ~10 −20 atm at 600 °C [11], ~10 −25 –10 −22 atm at 500 °C [11,46], and ~10 −30 atm at 400 °C [11]. Previous studies have suggested that the rate-controlling step in the corrosion of ferritic-martensitic steels in SCW is the outward diffusion of iron and that the inner layer generally plays the role of the protective barrier layer [7,8,10,12,30,33,51]. However, the inner layer grows into the metal phase at the metal/inner layer interface [52,53], and the cations diffusing outwards through the inner layer are not involved in the growth of the inner layer into the metal.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25]. A series of investigations on the corrosion resistances of these materials under supercritical and/or subcritical conditions [20,24,[26][27][28][29][30], reflected that no one kind of material can withstand corrosion at all conditions, but some exhibit perfect corrosion resistance under specific conditions, as given in Table 1. Thus, appropriate reaction conditions such as heteroatom types in feedstock, reaction temperature, and pressure should be optimized in order to minimize corrosion rate for a chosen reactor construction material.…”
Section: Corrosionmentioning
confidence: 99%
“…The dissolved metal cations combine with anions such as OH − in aqueous environments to form oxides or hydroxides; they then precipitate on specimens surface to form and/or thicken the outer layer [49]. Li et al [30] reported that the corrosion of Inconel 600 and Incoloy 825 in low density SCW containing sulfides also follows the solid-growth mechanism.…”
Section: Corrosionmentioning
confidence: 99%
“…According to the expected temperature and pressure, a predetermined volume of deoxygenated water was loaded in the autoclave. The detailed information about experimental apparatus and procedures can be obtained from our previous studies [12,13]. In order to explore the effects of operation parameters, such as temperatures, pressures, and initial pH value of experimental water, on the initial oxidation state of Super304H in supercritical water, tests with an exposure time of 40 h under various conditions were carried out.…”
Section: Experimental Conditionsmentioning
confidence: 99%